Oligonucleotide-capped nanoporous anodic alumina biosensor as diagnostic tool for rapid and accurate detection of Candida auris in clinical samples. Issue 1 (1st January 2021) - Pla, Luis; Santiago-Felipe, Sara; Tormo-Mas, María Ángeles; Ruiz-Gaitán, Alba; Pemán, Javier; Valentín, Eulogio; Sancenón, Félix; Aznar, Elena; Martínez-Máñez, Ramón
ABSTRACT: Candida auris has arisen as an important multidrug-resistant fungus because of several nosocomial outbreaks and elevated rates of mortality. Accurate and rapid diagnosis of C. auris is highly desired; nevertheless, current methods often present severe limitations and produce misidentification. Herein a sensitive, selective, and time-competitive biosensor based on oligonucleotide-gated nanomaterials for effective detection of C. auris is presented. In the proposed design, a nanoporous anodic alumina scaffold is filled with the fluorescent indicator rhodamine B and the pores blocked with different oligonucleotides capable of specifically recognize C. auris genomic DNA. Gate opening modulation and cargo delivery is controlled by successful DNA recognition. C. auris is detected at a concentration as low as 6 CFU/mL allowing obtaining a diagnostic result in clinical samples in one hour with no prior DNA extraction or amplification steps.